The influence of issues of management, government assistance, networking and employee turnover on SME performance in Malaysia : The impact of human capital as a mediator - Ravi, Ramasamy (2024)
Despite the significant contribution of small and medium-sized enterprises (SMEs) to the Malaysian economy, there is a gap in the literature regarding the impact of management, government assistance, networking, and employee turnover on SME performance, including the mediating role of human capital. This research aims to examine the influence of issues of management, government assistance, networking, and employee turnover on SME performance, and investigate the mediating role of human capital in this relationship. A self-administered questionnaire was completed by 178 Malaysian SME business owners between October 2022 and February 2023. Partial Least Squares-Structural Equation Modelling (PLS-SEM) was used for data analysis. The results show that issues of management and networking have no significant effect on SME performance, whereas government assistance, employee turnover and human capital have significant effects. Effective management practices, lower turnover rates, and investment in human capital development are critical to SME performance. Additionally, constantly improving the quality of human capital can lead to enhanced productivity. Human capital plays a crucial role as a mediator in the relationship between issues of management, government assistance, networking, employee turnover, and SME performance. Thus, continuous training and development programmes is vital for employee's competencies. In terms of theoretical contribution, this study applied the Resource-Based View Theory (RBV) as the underpinning theory and Institution Theory (IT) as the supporting theory in the proposed framework to examine the key factors that influence SME performance in Malaysia. SMEs should prioritise management practices and human capital development to improve their performance and competitiveness in the market